Crystal-field effects in Er 3 + - and Yb 3 + -doped hexagonal NaYF 4 nanoparticles - García Flores, A. F.; Matias, J.S.; Garcia, D. J.; Martínez, E. D.; Cornaglia de la Cruz, Pablo Sebastian; Lesseux, G.G.; Ribeiro, R. A.; Urbano, R. R.; Rettori, C. (American Physical Society, 2017)
Fil: García Flores, A. F.. Universidade Federal do ABC; Brasil